1969
DOI: 10.2105/ajph.59.8.1322
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of need and utilization rates for a public family planning program.

Abstract: This report is part of a continuing evaluation of the effectiveness of a county family planning program. It is concerned with the number of women currently in need of such services, and the proportion of these presently being served. Ways of defining the group in need are discussed, and special groups are considered. Reasons why women who are eligible do not use the services are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1970
1970
1974
1974

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
(3 reference statements)
0
3
0
Order By: Relevance
“…Several earlier studies (Kuralt, 1963;Frank and Tietze, 1965) have indicated that welfare recipients can be continuing and successful contraceptors, with about three-fourths of recipients in both samples remaining as clinic patients for several years or more. More recent studies have indicated that when distinctions are made between the very poor and the nearpoor, the very poor have been variously found to be equally likely to be covered by contraception (Udry, 1971), more likely to be covered by contraception (Siegel et al, 1969;Pomeroy and Torres, 1972), more likely to be sterilized (Siegel et al, 1969;Presser and Bumpass, 1972); less likely to be trying to get pregnant (Siegel et al, 1969), about as likely as other income groups to secure legal abortions (Smith et al, 1971;Kumabe, 1972); and as likely to visit physicians (Monteiro, 1973). …”
Section: Discussionmentioning
confidence: 99%
“…Several earlier studies (Kuralt, 1963;Frank and Tietze, 1965) have indicated that welfare recipients can be continuing and successful contraceptors, with about three-fourths of recipients in both samples remaining as clinic patients for several years or more. More recent studies have indicated that when distinctions are made between the very poor and the nearpoor, the very poor have been variously found to be equally likely to be covered by contraception (Udry, 1971), more likely to be covered by contraception (Siegel et al, 1969;Pomeroy and Torres, 1972), more likely to be sterilized (Siegel et al, 1969;Presser and Bumpass, 1972); less likely to be trying to get pregnant (Siegel et al, 1969), about as likely as other income groups to secure legal abortions (Smith et al, 1971;Kumabe, 1972); and as likely to visit physicians (Monteiro, 1973). …”
Section: Discussionmentioning
confidence: 99%
“…(59) Of 800 women interviewed, 63% were financially eligible for the family planning services and of these, 19% were classified as permanently not in need because of either infertility or sterilization. Of those in need (49% of the overall total) only 15% were active in the family planning clinic.…”
Section: Some Specific Program Evaluation Studies*mentioning
confidence: 99%
“…We have presented results of several of these investigations in a series of earlier papers. [1][2][3][4] This report focuses on changes relevant to family planning over the period 1967 to 1970-71 as determined by interviews of a cohort of women residing in 23 low-income census tracts in Charlotte. Associations between certain characteristics of the women, observed in 1967, and the extent of subsequent changes in selected knowledge, attitudes and practices relevant to family planning (KAP) and socioeconomic indices are explored.…”
Section: Introductionmentioning
confidence: 99%